The role of e-learning in LIS education : students' evaluations - Tot, Marko (Array, 2011)
The application of e-learning in Croatian universities has increased rapidly, with the introduction of the Bologna process to create the European Higher Education Area. The application of digital media for teaching and learning makes distance education for LIS professionals at the Faculty of Humanities and Social Sciences, University of Zagreb, possible. E-learning and traditional classroom learning have been combined to deliver library and information science (LIS) education. The aim of our research was to obtain a general overview of the LIS graduates’ expectations and experiences using Omega, a specific learning management system.